Uma oficina de matemática no ensino básico por meio da criptografia - MIRANDA, Ariane Andressa Noronha de Sousa (Universidade Federal do Tocantins, 2023)
This monograph addresses cryptography and its application in elementary and high school, th- rough the proposition of a workshop. In view of the importance of cryptography in maintaining